Age-Related Decrease in Amplitude of f Wave in Chronic Atrial Fibrillation - Fujiwara, Takamichi; Atarashi, Hirotsugu; Saitoh, Hirokazu; Hayakawa, Hirokazu (Nihon Rōnen Igakkai zasshi, 1987)
We assessed the relationship between fibrillatory wave (f wave) amplitude and age with 206 consecutive electrocardiograms in patients with chronic stable atrial fibrillation (131 men and 75 women, aged from 34 to 88). The electrocardiograms were divided into four groups in terms of underlying disease. Thirty-seven cases with mitral stenosis were classified as group I, 9 cases with valvular disease without mitral stenosis and atrial septal defect as group II, 59 cases with hypertensive heart disease and coronary artery disease as group III, and 101 cases with no obvious heart disease as group IV. The maximal f wave was measured both in leads II and V1 according to the technique employed by Peter RH, et al. The maximal f wave amplitude was 0.20±0.11mV (mean±Sd) in group I, 0.20±0.14mV in group II, 0.14±0.08mV in group III and 0.13±0.07mV in group IV, respectively. The amplitude of the f wave in lead II was inversely related with age in group I (r=-0.38, p<0.05), III (r=-0.28, p<0.05) and IV (r=-0.30, p<0.01) significantly and there was significant inverse relationship between f wave in V1 and age in groups III (r=-0.57, p<0.001) and IV (r=-0.33, p<0.01). In group II, no significant relationship was observed because of small number of cases. This suggests that aging is one of important factors which affect the f wave size in patients with chronic atrial fibrillation.